Fan pressure control in HVAC - Eng, Song Keat (2014)
Heat Ventilating and Air Conditioning (HVAC) is the major energy consumer in the commercial building. It can account for up to 40% of the total energy consumption. One of the prominent ways in reducing energy consumption is by using the Chilled Beam technology that uses water as the medium to extract heat from spaces as compared to the convention air technology (e.g.: fans).